T-cell-mediated signalling in immune, inflammatory and angiogenic processes: the cascade of events leading to inflammatory diseases. - Monaco, C; Andreakos, E; Kiriakidis, S; Feldmann, M; Paleolog, E (2004)
In the last decade, the understanding of the molecular mechanisms of regulation of the inflammatory process in chronic inflammatory diseases has moved remarkably forward. Recent evidence in various fields has consistently indicated that T-cells play a key role in initiating and perpetuating inflammation, not only via the production of soluble mediators but also via cell/cell contact interactions with a variety of cell types through membrane receptors and their ligands. Signalling through CD40 and CD40 ligand is a versatile pathway that is potently involved in all these processes. In this article, we review how T-cells become activated by dendritic cells or inflammatory cytokines, and how these T-cells activate, in turn, monocytes/macrophages, endothelial cells, smooth muscle cells and fibroblasts to produce pro-inflammatory cytokines (tumour necrosis factor alpha, interleukin-6), chemokines (interleukin-8, monocyte chemotactic protein-1), tissue factor, the main initiator of the coagulation cascade in vivo, and finally matrix metalloproteinases, responsible for tissue destruction. Moreover, we discuss how CD40 ligand at inflammatory sites stimulates fibroblasts and tissue monocyte/macrophage production of VEGF, leading to angiogenesis, which promotes and maintains the chronic inflammatory process. This cascade of events is discussed in the context of disease initiation/progression, with particular reference to atherosclerosis and rheumatoid arthritis, and to potential novel therapeutic targets for their treatment.